Complexity and dissonance: Islamic law states and the international order - Powell, Emilia Justyna (International studies review, 2022)
It is safe to say that much of international law—the bedrock of the international order—has been shaped by the Western legal doctrine. How does the Islamic legal tradition relate to international law? What are Islamic law states’ (ILS) stance toward the global order and international relations? This article offers a fresh perspective of similarities and differences between international law and Islamic law. ILS’ patterns of commitments to a number of international treaties and institutions reveal a nuanced picture of these states’ position in the contemporary global order. I bring together the English-language-dominated field of international relations and the Arabic-language literature on global order and Islamic law. I trace Islam's contributions to international law and argue that international law and Islamic law share more similarities than they are given credit for. However, the inherent diversity of Islamic law and the lack of an authoritative body of Islamic international law muddle effects of historical cross-fertilization between Islamic law and international law. In reality, ILS’ position in the global order is not about a fundamental clash of values. A much more intricate picture emerges. In an important way, this paper sketches an emerging research agenda for understanding ILS’ position in the modern global order.